Igreja Universal do Reino de Deus na tv: pseudo-pentecostalismo e sacralização do sucesso - Franco, Washington Santos (2007)
Having as its background Brazilian Pentecostalism, the Universal Church of the Kingdom of God combines several elements from the diversified Brazilian religious matrix and became an expression of a syncretism religiosity related to practices of magic-religious content, using a speech that makes success and prosperity the sacred external signs of God’s visitation. Using television as a midiatic resource that church (IURD) strategically propagates a religious speech based in a dualistic theodicy from which the main purpose is the routinization of the devil intervention on individual daily life, as well of the liberation of such evil actions by the mediation of its bishops and pastors. This manicheistic scenario of spiritual warfare the individual person is constantly induced to choose which territory wants to be in: the “territory of Good” vs. the “territory of Evil”, because this option may result in success and prosperity or in all sorts of suffering, to choose this territory of the Good and to take this decision with sacrifice and a claiming faith results in a prosperous and blessed life. In that Church (IURD) prosperity and the fruition and consumer goods are conditions of an authentic faith, whose speech converges with the market ideology mating possible the presence of elective affinities between them.